(untitled) (Journal of Economic Research & Business Administration, 2015)
The article considers mediation as a method of conflict resolution in Kazakhstan as well the development of a unified concept of mediation in Kazakhstan, to provide quality services to resolve and prevent conflicts in various areas. Mediation is a court procedure and a link designed to work for the removal of the conflict, relaxation of tension in society. The scope of the mediation may be: civil, labor, corporate, commercial, family, educational, and other disputes. Today, the public does not develop a common understanding of the nature of mediators. Most people hardly know the profession of mediator and as a result, it has a low level of confidence. To maximize the development of mediation in the country, you need not the assumption of corruption, public information and specific information available, the creation of a professional base for the training of competent professionals, the development of a unified concept of mediation in Kazakhstan, and the provision of quality services to resolve and prevent conflicts in various areas, the development of civil society and a comprehensive study of the practical experience of other countries that have successfully mediation mechanisms. Mediation as a method of conflict resolution is notable, his liberalism. The conflict should be considered from three standpoints: legal, economic, and personal.